Klinefelter syndrome as a window on the etiology of language and communication impairments in children: the neuroligin-neuroexin hypothesis - Bishop, D; Scerif, G (Wiley-Blackwell, 2011)
Aim: To compare the phenotype in Klinefelter syndrome (KS) with (a) specific language impairment (SLI) and (b) XXX and XYY trisomies. Methods: Phenotypes of KS, XXX and XYY were based on data from a systematic review of neurodevelopmental outcomes plus a recent parent survey. Phenotype of SLI was based on a published survey of children attending a special school. Results: There are close similarities between the KS phenotype and SLI. Furthermore, a minority of children with KS have features of autistic spectrum disorder. Similar language and communication problems are seen in the other two sex chromosome trisomies (SCTs), XXX and XYY. Conclusion: We propose the neurexin-neuroligin hypothesis, based on the observation that neuroligin genes, which occur on both X and Y chromosomes, are involved in the same synaptic networks as neurexin genes with common variants that affect risk for SLI and autism. According to our hypothesis, the effect of a triple dose of neuroligin gene product will be particularly detrimental when it occurs in conjunction with specific variants of neurexin genes on other chromosomes. This speculative proposal demonstrates the potential of illuminating the etiology of common neurodevelopmental disorders by studying children with SCTs.